PENGARUH PENGETAHUAN AKUNTANSI DAN PENGALAMAN PEMILIK USAHA TERHADAP KUALITAS LAPORAN KEUANGAN UMKM BERDASARKAN SAK EMKM - As'adi As'adi; Achmad Nur Fuad Chalimi (Unitri Press, 2020)
The study was conducted to determine the effect of accounting knowledge and experience of business owners on the quality of MSME financial reports based on SAK EMKM. The results of the significant value of accounting knowledge and business experience are 0.002 and 0.000. This value is less than the Alpha value, which is 0.05, which means there is positive influence on accounting knowledge and business experience report quality MSMEs owner financesiPasuruan Regency. The findings obtained by the researcher refer to the results of the analysis which states the importance of accounting knowledge and business experience for MSMEs in Pasuruan Regency. The variables studied to make a positive contribution to the quality of financial reports produced by MSMEs. For this reason, it is necessary to provide continuous guidance to MSMEs business owners in maintaining the quality of the financial reports they produce